Development of spinal deformities in the tight-skin mouse - Li, B; Urban, J; Yu, J (Springer Nature, 2017)
Tight-skin (TSK) mice are commonly used as an animal model to study the pathogenesis of Marfan syndrome (MFS), but little is known of their skeletal phenotype and in particular of the development of the spinal deformities, common in MFS. Here we examined growth of the axial skeletons of TSK and wild-type(B6) mice during their period of rapid growth. The whole bodies of mice, 4-12 weeks of age, were scanned after sacrifice, by micro-computed tomography (microCT). We reconstructed three-dimensional models of the spine and ribs, and measured vertebral body heights and rib lengths using the Mac-based image-processing software "OsiriX". Although the TSK mice were smaller than the B6 mice at 4 weeks, they experienced an early growth spurt and by 8 weeks the height, but not the width, of the vertebral body was significantly greater in the TSK mice than the B6 mice. Measurement of the angles of scoliotic and kyphotic curves post-mortem in the mice was problematic, hence we measured changes that develop in skeletal elements in these disorders. As a marker of kyphosis, we measured anterior wedging of the vertebral bodies; as a marker for scoliosis we measured asymmetries in rib length. We found, unlike in the B6 mice where the pattern was diffuse, wedging in TSK mice was directly related to spinal level and peaked steeply at the thoracolumbar junction. There was also significant asymmetry in length of the ribs in the TSK mice, but not in the B6 mice. The TSK mice thus appear to exhibit spinal deformities seen in MFS and could be a useful model for gaining understanding of the mechanisms of development of scoliosis and kyphosis in this disorder.